THE ROLE OF CONTEMPORARY HR TECHNOLOGIES IN IMPROVING BUSINESS PERFORMANCE - Mirzabdullayev, Rasuljon; Sarimsakov, Bakhtiyor (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2025)
This article analyzes the impact of implementing modern HR technologies on the efficiency of enterprises. As digital transformation accelerates, tools such as automation, artificial intelligence, HR analytics, and cloud-based HR platforms are becoming key drivers of effective human resource management. The study evaluates how the adoption of these technologies influences workforce productivity, improves decision-making, optimizes recruitment and training processes, and strengthens employee engagement. The findings reveal that the integration of advanced HR technologies significantly enhances operational efficiency and contributes to the overall competitiveness of enterprises.